2015
DOI: 10.1007/s00300-015-1847-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of summer precipitation and summer temperature in establishment and growth of dwarf shrub Betula nana in northeast Siberian tundra

Abstract: It is widely believed that deciduous tundrashrub dominance is increasing in the pan-Arctic region, mainly due to rising temperature. We sampled dwarf birch (Betula nana L.) at a northeastern Siberian tundra site and used dendrochronological methods to explore the relationship between climatic variables and local shrub dominance. We found that establishment of shrub ramets was positively related to summer precipitation, which implies that the current high dominance of B. nana at our study site could be related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
50
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 56 publications
(81 reference statements)
12
50
2
Order By: Relevance
“…Spring and summer precipitation can be a growthlimiting factor for tundra shrubs at some Arctic and alpine tundra sites (rayBaCK et al 2010;liang et al 2012;KeuPer et al 2012;li et al 2016), but we did not find a positive influence of spring or summer precipitation for the site-species combinations studied here. However, precipitation is spatially highly variable and Arctic precipitation records are restricted to a few meteorological stations which limits data availability to gridded climate datasets (MyerS-SMitH and MyerS 2018).…”
Section: Discussioncontrasting
confidence: 42%
“…Spring and summer precipitation can be a growthlimiting factor for tundra shrubs at some Arctic and alpine tundra sites (rayBaCK et al 2010;liang et al 2012;KeuPer et al 2012;li et al 2016), but we did not find a positive influence of spring or summer precipitation for the site-species combinations studied here. However, precipitation is spatially highly variable and Arctic precipitation records are restricted to a few meteorological stations which limits data availability to gridded climate datasets (MyerS-SMitH and MyerS 2018).…”
Section: Discussioncontrasting
confidence: 42%
“…The predominance of birch ( Betula nana L.) shrubs in dry northeastern Siberia could also be related to high summer precipitation (Li et al. ). By contrast, our study area is characterized by cold and dry alpine conditions with high radiation and evaporation levels (Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Li et al. ). In addition, biotic interactions and changes in land management are important for shrub coverage (Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrub growth is also affected by a multitude of factors. Several studies have shown dependencies upon growing season temperature, precipitation and/or drought indices (Weijers et al 2010(Weijers et al , 2012Blok et al 2011;Buras et al 2012;Myers-Smith et al 2015;Lehej cek et al 2016;Li et al 2016). Shrub growth is further affected by the amount of photosynthetic active radiation and thus solar radiation received within the growing season.…”
Section: Shrub Wood Anatomy As Suitable Proxy For Gris-melt?mentioning
confidence: 99%